ผลเฉลยที่เป็นไพรม์พีเรียด 4 และจุดสมดุลของระบบสมการเชิงผลต่าง x_{n+1} = |x_n| - y_n – 2 และ y_{n+1} = x_n - |y_n| +1 โดยเงื่อนไขเริ่มต้น x_0 = 0 และ 0 < y_0 < 1/2 Prime Period 4 and Equilibrium Solutions of a System of Difference Equations and with In - ติ๊กจ๊ะ, วิโรจน์; วาทา, ทรรศวรรณ; สุขมามอญ, ศศิประภา; อินทรประพันธ์, ศิริเพชรก์ (Science Essence Journal, 2017)
บทคัดย่อ บทความนี้ศึกษาผลเฉลยของระบบสมการเชิงผลต่างเชิงเส้นเป็นช่วงและหาผลเฉลยที่เป็นไพรม์พีเรียด 4 พร้อมทั้งจุดสมดุลของระบบสมการ x_{n+1} = |x_n| - y_n – 2 และ y_{n+1} = x_n - |y_n| +1 โดยเงื่อนไขเริ่มต้น x_0 = 0 และ 0 < y_0 < 1/2 จุดสมดุลของระบบสมการเชิงผลต่างดังกล่าวคือ หาได้จากการใช้โปรแกรมคอมพิวเตอร์และการคำนวณโดยตรง และนอกจากนั้นระบบสมการดังกล่าวมีผลเฉลยที่เป็นไพรม์พีเรียด 4 และเราพิสูจน์ว่าผลเฉลยของระบบสมการที่มีเงื่อนไขเริ่มต้นดังกล่าวเป็นไพรม์พีเรียด 4 หรือจุดสมดุลในที่สุดโดยการหาแบบรูปในรูปของจำนวนเต็มบวกและใช้หลักอุปนัยเชิงคณิตศาสตร์ในการพิสูจน์ - - - Prime period 4 and equilibrium solutions of a system of difference equations x_{n+1} = |x_n| - y_n – 2 and y_{n+1} = x_n - |y_n| +1 with initial conditions x_0 = 0 and 0 < y_0 < 1/2 ABSTRACT The aim of this article is to study the solution of a piecewise linear system of difference equations, prime period 4 and equilibrium point of system x_{n+1} = |x_n| - y_n – 2 and y_{n+1} = x_n - |y_n| +1 with initial conditions x_0 = 0 and 0 < y_0 < 1/2. After observing via computer program and some direct computations, we found that the equilibrium point of the system is (-1, 0) and we also found that there are two prime period 4 solutions. We prove that every solutions with the initial condition is eventually prime period solutions or equilibrium point by finding the pattern of solutions that involve the natural number. We prove the inductive statement by using the mathematical induction.